Correlation of Iron Overload and Glomerular Filtration Rate Estimated by Cystatin C in Patients with β-Thalassemia Major. (October 2014) - Al-Khabori, Murtadha; Bhandari, Sunil; Al-Rasadi, Khalid; Mevada, Surekha; Al-Dhuhli, Hamoud; Al-Kemyani, Nasser; Daar, Shahina
Abstract Historically, renal involvement has not been a commonly recognized complication in patients with β-thalassemia major (β-TM). Herein, we studied the impact of iron overload on glomerular filtration rate (GFR) estimated by cystatin C based GFR (Cyst C eGFR). We enrolled 149 patients with β-TM in a cross sectional study in a single center in Oman. We investigated the correlation between measurement of serum ferritin and Cyst C eGFR. We used univariable linear regression to study the impact of serum ferritin on Cyst C eGFR and backwards stepwise regression to adjust for potential confounders. We included 78 males and 71 females with a mean age of 17.3 ± 9 years (range 2.5–38.5). Seventeen patients had diabetes mellitus. Patients were taking deferiprone (DFP) and deferoxamine (DFO) (26 patients), DFP (58 patients), deferasirox (DFX) (62 patients) and one patient was taking only DFO. There was a very weak negative linear relationship between serum ferritin and Cyst C eGFR (correlation coefficient −0.25). In the univariable analyses, serum ferritin (p = 0.004), diabetes status (p < 0.001) and chelation therapy (p < 0.001) were statistically significant. In the multivariable model, age (p = 0.033), chelation with DFX (p = 0.05) and diabetes status (p < 0.001) were statistically significant. We found a very weak inverse linear correlation between serum ferritin and Cyst C eGFR. However, when concomitant use of chelation therapy was considered, serum ferritin did not associate with glomerular function. Prospective and larger studies are needed to confirm these findings.